2014
DOI: 10.1007/s00592-014-0638-3
|View full text |Cite
|
Sign up to set email alerts
|

Effects of exenatide, insulin, and pioglitazone on liver fat content and body fat distributions in drug-naive subjects with type 2 diabetes

Abstract: Ectopic accumulation of lipids in nonadipose tissues plays a primary role in the pathogenesis of type 2 diabetes mellitus (T2DM). This study was to examine the effects of exenatide, insulin, and pioglitazone on liver fat content and body fat distributions in T2DM. Thirty-three drug-naive T2DM patients (age 52.7 ± 1.7 years, HbA1c 8.7 ± 0.2 %, body mass index 24.5 ± 0.5 kg/m(2)) were randomized into exenatide, insulin, or pioglitazone for 6 months. Intrahepatic fat (IHF), visceral fat (VF), and subcutaneous fat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

10
67
1
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 61 publications
(79 citation statements)
references
References 37 publications
10
67
1
1
Order By: Relevance
“…LFC decreases in insulin‐naïve T2D patients randomized to glargine were similar to those reported by Tang et al in insulin‐naïve T2D patients . Decreases in LFC have also been reported with other conventional basal insulins (including biphasic aspart 70/30 and biphasic lispro 75/25) in insulin‐naїve T2D patients. Among these studies, only Lingvay et al reported a statistically significant decrease in ALT with insulin treatment.…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…LFC decreases in insulin‐naïve T2D patients randomized to glargine were similar to those reported by Tang et al in insulin‐naïve T2D patients . Decreases in LFC have also been reported with other conventional basal insulins (including biphasic aspart 70/30 and biphasic lispro 75/25) in insulin‐naїve T2D patients. Among these studies, only Lingvay et al reported a statistically significant decrease in ALT with insulin treatment.…”
Section: Discussionsupporting
confidence: 86%
“…These results demonstrate that BIL, with reduced peripheral insulin activity (Fig. in) compared with glargine, does not decrease LFC, in contrast to several other basal insulins . Treatment with BIL resulted in higher LFC values compared to glargine in both T1D and T2D.…”
Section: Discussionmentioning
confidence: 62%
“…This inconsistency reflects the different fat locations and individuals used in the studies. We studied epididymal fat, as exenatide has been revealed to reduce visceral rather than subcutaneous fat content [26]. The effect of GLP-1 on lipolysis might only exist in pathological conditions, and pharmacologically GLP-1 is likely to act in visceral rather than subcutaneous fat.…”
Section: Discussionmentioning
confidence: 99%
“…The null hypothesis was that the treatment groups did not differ from each other with respect to the primary endpoint. A priori sample size calculations were based on the ability to detect an 18.6%, 18.6%, and 13.7% absolute clinical difference in liver fat before and after the intervention of liraglutide, sitagliptin, and insulin glargine, respectively . With a deviation estimate of 5.5% obtained from a similar study, we estimated that 22 patients in each group would be required, for a total of 66 patients (α = 0.05, β = 0.15).…”
Section: Methodsmentioning
confidence: 99%